Emotional Intelligence in Elementary School Children. EMOCINE, a Novel Assessment Test Based on the Interpretation of Cinema Scenes - Sastre, Santiago; Artola, Teresa; Alvarado, Jesús M. (Frontiers in Psychology, 2019)
The aim of the present study was to validate a new procedure for measuring perception and comprehension components of the emotional intelligence (EI) in 1,448 children, aged between 8 and 13 years, from elementary schools by using EMOCINE test. This new tool consists of watching 15 film clips and interpreting them according to children´s own-emotional perception and comprehension. After completing the test, the participants were classified, according to their responses and by using the latent class analysis, as naïve (16.1%), over-interpretative (33.5%) and sensitive (50.4%). An increase in sensitive responses was observed depending on participants sex (girls higher than boys), and academic grade (increasing over the grades). Participants from the sensitive latent class had a significant higher academic performance and a better behavior in the school/classroom, compared with those from naïve and over-interpretative groups. Likewise, significant differences between latent classes were observed in many psychological, emotional, and behavioral problems (mainly between sensitive versus insensitive by naivety) such as: depression, posttraumatic symptomatology, attention problems, aggression, family problems, problems with school, problems with classmates, integration and social competence, index of emotional problems, index of contextual problems, index of personal resources, and global index of problems. In conclusion, EMOCINE is a novel and relevant tool for the measurement of the perception and comprehension components of EI. It may be considered as reliable and valid. The test, employing film clips, is more realistic and motivating than others using static images or written descriptions. Moreover, the test can predict or identify emotional and behavior problems.